Description Of Factors Influence the lowering utilization IUD Contraception in Desa Rambah Samo Barat Rokan Hulu - ALDRIANA, NANA (Jurnal Martenity and Neonatal, 2013)
The utilization of IUD in Indonesia is still less than other types of contraception. BKKBN said from 29 million users of contraception in Indonesia, only 8% used IUD. This study objective is to description factors influence the lowering utilization of IUD. This is descriptive study with cross sectional types. This Reserch has done in July 19th-25th 2012 using 82 respondents which used contraception. Samples takes by simple random sampling technique